История изучения. История народов. Социалистическое строительство - Алексеев Н. М. (1958)
Экземпляры: КХ (20120927) / Инвентарный номер: 227532 / Сис.шифр: 016:91 / Авт.знак: Б 59 / ГРНТИ: 39 / ББК: 9